2022
DOI: 10.1002/art.42065
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Semaphorin 3B in a Serum‐Induced Arthritis Model and Reduced Levels in Patients With Rheumatoid Arthritis

Abstract: Objective. Semaphorin 3B (Sema3B) decreases the migratory and invasive capacities of fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA) and suppresses expression of matrix metalloproteinases. We undertook this study to examine the role of Sema3B in a mouse model of arthritis and its expression in RA patients.Methods. Clinical responses, histologic features, and FLS function were examined in wild-type (WT) and Sema3B −/− mice in a K/BxN serum transfer model of arthritis. Protein and messenger RNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Therefore, the CD13/B1R axis involving RASF may contribute to the inflammatory activation of RASF. Semaphorin 3B was previously shown to reduce migration and invasion as well as the expression of matrix-degrading enzymes by human RASF, properties that could be confirmed recently in animal models [25]. Here, semaphorin 3B knockout animals showed a significantly higher severity of serum-induced arthritis compared with wildtype controls whereas administration of semaphorin 3b reduced clinical severity in this model.…”
Section: Rheumatoid Arthritis Synovial Fibroblasts Are Activated By P...supporting
confidence: 65%
“…Therefore, the CD13/B1R axis involving RASF may contribute to the inflammatory activation of RASF. Semaphorin 3B was previously shown to reduce migration and invasion as well as the expression of matrix-degrading enzymes by human RASF, properties that could be confirmed recently in animal models [25]. Here, semaphorin 3B knockout animals showed a significantly higher severity of serum-induced arthritis compared with wildtype controls whereas administration of semaphorin 3b reduced clinical severity in this model.…”
Section: Rheumatoid Arthritis Synovial Fibroblasts Are Activated By P...supporting
confidence: 65%
“…Histological analysis was performed as previously described ( 28 , 29 ). Right hind limbs were prepared for histological analysis by dissecting the skin and sectioning the ankle joints.…”
Section: Methodsmentioning
confidence: 99%
“…Both in K/BxN STIA and in RA patients, delayed progression of joint damage upon administration of recombinant sema3B was observed. These data clearly suggest that K/BxN STIA can be effectively modulated in preclinical studies once the target mechanism has been identified ( 63 ).…”
Section: Discussionmentioning
confidence: 92%